Pertumbuhan dan Sintasan Juvenil Teripang Pasir Holothuria scabra pada Pemeliharaan Dengan dan Tanpa Rumput Laut Gracilaria sp., Menggunakan Keramba Apung dan Tancap di Tambak - Dedy Kurnianto; Lisa F Indriana; Abdul Wahab; Syafriyadi Hafid; Balkam F Badi, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Growth and Survival of Sandfish Holothuriascabra Juveniles Grown with and without Seaweed Gracilaria sp., using Floating and Fixed Hapas in Earthen Pond. Holothuriascabra known as sandfish have long been used for pharmaceutical, cosmetic, and food industries.Juveniles production is one of the ways to address the problem of raw material availability due to declining sandfish population in the wild. This research aimed to determine growth performance and survival of sandfish juveniles reared with and without seaweed Gracilaria sp. using floating and fixed hapas in earthen pond. The research was conducted from May to September 2014. A completely randomized design was used to arrange 12 hapas of four treatments groups with three replicates including floating hapas without Gracilaria sp. (ATR), floating hapas with Gracilariasp. (ADR), fixed hapas without Gracilaria sp. (TTR) and fixed hapas with Gracilaria sp. (TDR). Some parameters was observed includingweight increment, Growth Rate (GR),Specific Growth Rate(SGR), Biomass, Survival, and Water Quality. The result showed that GR and SGR were not significantlydifferent among treatments (P>0.05). Survial and Biomass showed significant difference among treatments (P <0.05). ATR has the highest GR, SGR, survival, dan biomass whereas TDR has the lowest GR, SGR, survival, dan biomass. Water quality parameters were in optimal range for sandfish rearing. AddedGracilaria sp.tend to inhibitGR, SGR, survival, dan biomass.